Revisionisme Sejarah Jepang terhadap Peristiwa Pembantaian Nanjing - Nanda, Ni Putu Rianti Sukma; Purnomo, Joko (Department of International Relations, Brawijaya University, 2020)
This study examines Japan's historical revisionism related to the Nanjing Massacre during its 1937 invasion in the People's Republic of China. In 2015, UNESCO's response to include the Nanjing Massacre in the